Effect of two bleaching methods on the microleakage of resin composite resin restorations - F Farahnakian; SM Mousavinasab; P Mirzakucheki (Isfahan University of Medical Sciences, 2008)
Introduction: In patients requesting to bleach their teeth, bleaching treatment might affect microleakage of present restorations. Technique and concentrations of applied bleaching and bonding agents are some effective factors on microleakage of composite restorations. The aim of this study was to evaluate the effect of bleaching method on microleakage of resin composite restorations.Methods and Materials: 48 extracted carries free human premolars were selected and randomely divided into 4 groups. Class V cavities were prepared on buccal and lingual surfaces, with gingival margins located 1 mm below CEJ. In group one Cleatfil, SE- bond and Single bond applied on buccal and lingual surfaces respectively, and cavities restored by Z 250 resin composite. In group two, the cavities were restored as in group one and then were kept in distilled water for a period of one month. In group three, all the stages resembled group two and home bleaching regimen was used. In group four, all the stages resembled group two, but samples subjected to in office bleaching regimen. All the samples were thermocycled and examined for microleakage. Data analyzed using Wilcoxon, Kkruskal-wallis and Man-Whitney U tests (a = 0.05).Results: Single bond compared to SE- bond provided the best post bleaching results regarding microleakage. The amount of microleakage was higher in office bleach technique in both margins.Discussion: Single bond showed the best results regarding post bleaching microleakage. Bleaching had a negative effect on microleakage that was higher in office technique.Key words: Carbamide Peroxide, Resin Composite, Microleakage, Dental Bleaching